2019
DOI: 10.1101/684290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pac1/LIS1 promotes an uninhibited conformation of dynein that coordinates its localization and activity

Abstract: 45Cytoplasmic dynein is a minus end-directed microtubule motor that transports myriad 46 cargos in various cell types and contexts. How dynein is regulated to perform all these 47 62Cytoplasmic dynein is an enormous minus end-directed microtubule motor 63 complex that transports numerous cargoes. At first glance, this motor seems 64 exceedingly complex in terms of its architecture, size, and reliance on accessories and 65 regulators for proper activity. For instance, processive single molecule motility of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
(189 reference statements)
2
10
0
Order By: Relevance
“…This finding explains the requirement for Lis1 for transport initiation in vivo 34 , 38 . Consistent with two recent reports that studied the role of Lis1 in mammalian and yeast dynein-dynactin motility 55 , 56 , we show that Lis1’s ability to promote the association of dynein with dynactin also favors the adoption of the two-motor state, which accounts for more frequent stepping and higher force generation per complex. The increased probability of recruiting two dyneins to dynactin also means that Lis1 induces more effective competition against kinesin in a tug-of-war, a result consistent with an increase in anterograde velocity observed when Lis1 is inhibited in cells 37 , 39 .…”
Section: Discussionsupporting
confidence: 92%
“…This finding explains the requirement for Lis1 for transport initiation in vivo 34 , 38 . Consistent with two recent reports that studied the role of Lis1 in mammalian and yeast dynein-dynactin motility 55 , 56 , we show that Lis1’s ability to promote the association of dynein with dynactin also favors the adoption of the two-motor state, which accounts for more frequent stepping and higher force generation per complex. The increased probability of recruiting two dyneins to dynactin also means that Lis1 induces more effective competition against kinesin in a tug-of-war, a result consistent with an increase in anterograde velocity observed when Lis1 is inhibited in cells 37 , 39 .…”
Section: Discussionsupporting
confidence: 92%
“…We propose this based on our data showing that Open dynein has a higher affinity for Lis1 and because the structure of Phi dynein is incompatible with Lis1 binding at site ring . Recent work in Aspergillus nidulans 46 and Saccharomyces cerevisiae 47 also supports this. Second, Lis1 may favor a conformation of dynein that is primed to assemble the fully activated complex ( Fig.…”
mentioning
confidence: 59%
“…Together our work suggests that Lis1 promotes the formation of human dynein/ dynactin/ activating adaptor complexes containing two dynein dimers. Experiments in human cells 18 , Drosophila embryos 24 , Xenopus extracts 39 , Aspergillus nidulans 46 , and yeast 47 showed that Lis1 is required for the interaction of dynein and dynactin with each other and/or with their cargos. Our work offers a biochemical explanation for this requirement for Lis1.…”
mentioning
confidence: 99%
“…In comparison, mammalian dynein heavy chain is auto-inhibited if it is not transporting cargos, and activation of its motility requires its association with dynactin and a cargo adaptor protein (referred to as dynein transport machinery). The formation of the dynein transport machinery is strongly favored by regulatory proteins, such as Lis1 [56][57][58] . Cargo adaptors, such as BICDR, BICD2, Hook3 and TRAK1-2, contain a long coiled-coil region that links the tail of the heavy chain to the actinlike filament of dynactin.…”
Section: Figure 2 Mechanochemical Cycle Of a Dynein Monomermentioning
confidence: 99%
“…Consistent with its asymmetric force-dependent detachment from MT, dynein moved faster towards the minus-end compared to the plus-end under the same magnitude of force ( Figure 8b) 83,84,92 . 51,50,59,53,41,35,48,46,43,54,62,47,82,68,56,92,85,44,45,78 The average velocity (V, positive velocities are in the minus-end direction) at a given force is given by:…”
Section: Dynein Responds Asymmetrically To Assisting and Hindering Loadsmentioning
confidence: 99%